Randomized response and indirect questioning techniques in surveys - Chaudhuri, Arijit, 1940- (Boca Raton : Chapman and Hall/CRC, 2010)
"A long-standing problem in survey research is that respondents are often reluctant to give truthful answers to sensitive questions. The randomized response technique (RRT) addresses this problem by guaranteeing respondents' anonymity and minimizing their discomfort. The key to this is that respondents determines which question they answer using some probability device, such as a coin flip or a roll of the dice. In this book, one of the world's leading experts on the subject summarizes the current state of the theory and practice of RRT. He examines how to extend the theory to situations employing unequal probability sampling"--
Includes bibliographical references and index.
rua 21/05/13
Loans
Keywords: Sampling (Statistics); Surveys -- Statistical methods; MATHEMATICS / Probability & Statistics / General